#MeToo a Burkean analysis of the online self-disclosure posts of female Filipino sexual violence survivors on Facebook and Twitter - Bocobo, Therese Gabrielle E.; De Luna, Teresa Paula (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
The #MeToo campaign is an online movement that revolutionized-and publicized-the otherwise private act of self-disclosure for sexual violence survivors from all over the globe. Though it's had its humble beginnings as a grassroots movement intended to provide healing for abused women of color in low-income communities it has since evolved into a leviathan campaign involving millions of sexual violence survivors from various backgrounds who have publicly disclosed their experience with abuse towards a common goal of calling out perpetrators and, ultimately, eradicating systemic failures that allow for such abuse to proliferate. Anchored in a localized setting against a backdrop of current events, the study's main purpose was to find out how the #MeToo campaign impacts the act of self-disclosure for Filipina sexual violence survivors. Having adopted a Burkean rhetorical approach combined with a framework provided by Chaudoir and Fisher's Disclosure Processes Model (2010), the study analyzed the overall drama of the #MeToo campaign through the elements of Kenneth Burke's pendtad: the act, actor, agent, agency, and purpose. Then, using a Purpose-Act ratio, the study found that the public nature of the movement's approach-focused antecedent goals has surmounted the typically private nature of self-disclosure to meet, in effect, the public act of calling out perpetrators and failures in the system towards the fulfillment of the movement's purpose. As a complement, a thematic analysis of twenty-one #MeToo statements published by Filipina sexual violence survivors on Facebook and Twitter yielded findings that show how the #MeToo campaign serves as an avenue for expression, empowerment, and connections (or networking) for survivors of sexual violence, utilizing the mediating processes of a)alleviation of inhibition b)social support, and c)changes in social information to establish a conducive digital environment for public self-disclosure.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.